KONSELING OLEH KADER POSYANDU MENINGKATKAN PRAKTIK IBU DALAM PEMBERIAN MAKAN BAYI DAN ANAK USIA 6-24 BULAN DI DESA PAGELARAN, KECAMATAN CIOMAS, BOGOR, INDONESIA - Siti Mutia Rahmawati; Siti Madanijah; Faisal Anwar; Risatianti Kolopaking (GIZI INDONESIA, 2019)
The feeding practices of infants and children (PMBA) at the age of 6-24 months should be done correctly and appropriately. Errors in feeding in this period may cause malnutrition and stunted. The purpose of this study was to determine the effect of counseling by Posyandu cadres on changes in infant and child feeding practices (PMBA) done by mothers among infants and children aged 6-24 months. Quasi-experimental research design with one group pre-post test design was applied and envolving 78 mothers of infants and children aged 6-24 months. Data on feeding practices of infants and children were obtained by interviewing mothers using a structured questionnaire covered data of mothers, babies and children, health status and growth, and the practice of breastfeeding and complementary feeding as well as hygiene were also collected. PMBA practices were then being scored covered all indicators, then categorized into 3 groups : being good if the score = 80, enough 60-79.9 and less if the score is 60. T-test and Wilcoxon rank test were used at the significance level of 0.05. The average value of infant and child feeding practices by caregivers before counseling was 70.0 and increased to 75.2 after counseling. PMBA practices of mothers categorized as good increased from 25.3% to 46.7%. This study showed that there was an effect of counseling on the improvement of feeding practices for baby by mother/ caregivers (p 0.01). In conclusion counseling carried out by Posyandu cadres may improve the practice of PMBA by mother for their infants and children at the aged 6-24 months.